2018
DOI: 10.1002/anie.201811314
|View full text |Cite
|
Sign up to set email alerts
|

Synthesis and Properties of a Highly Congested Tri(9‐anthryl)methyl Radical

Abstract: The synthesis of persistent, neutral organic radicals is challenging because of their inherent reactivities. Herein, we report the synthesis and characterization of a highly congested mesityl‐substituted tri(9‐anthryl)methyl (TAntM) radical (1). The scaffold was successfully synthesized by circumventing the steric hindrance imposed by the bulky groups surrounding the central methyl carbon atom. The radical has a threefold propeller structure, and the unpaired electron is mainly localized on the central carbon … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
49
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 63 publications
(54 citation statements)
references
References 34 publications
4
49
1
Order By: Relevance
“…The reaction of 2 d with SnCl 2 ⋅2 H 2 O afforded not a radical monomer Ant‐DPM but a tail‐to‐tail σ‐dimer, (Ant‐DPM) 2 , in good yield (62 %, Scheme ). The facile dimerization of Ant‐DPM probably arises from the flexibility of the diphenylmethyl skeleton compared with the other radicals, resulting in the σ‐dimer formation at 10‐position of the anthryl group . Thus, the rigidity of the tricyclic radical scaffold plays an important role in the persistence of Ant‐5 , Ant‐6 , and Ant‐7 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of 2 d with SnCl 2 ⋅2 H 2 O afforded not a radical monomer Ant‐DPM but a tail‐to‐tail σ‐dimer, (Ant‐DPM) 2 , in good yield (62 %, Scheme ). The facile dimerization of Ant‐DPM probably arises from the flexibility of the diphenylmethyl skeleton compared with the other radicals, resulting in the σ‐dimer formation at 10‐position of the anthryl group . Thus, the rigidity of the tricyclic radical scaffold plays an important role in the persistence of Ant‐5 , Ant‐6 , and Ant‐7 .…”
Section: Resultsmentioning
confidence: 99%
“…Interestingly, a toluene solution of the σ‐dimer of Ant‐5 showed a slight color change from pale yellow to purple at high temperature (100 °C), indicating dissociation from σ‐dimer to a monomeric radical. In addition, a mechanical grinding also caused the dissociation of the Ant‐5 σ‐dimer, which can be recognized by a color change from yellow to purple (Figure S7, Supporting Information). It is noteworthy that these features could not be observed for the σ‐dimers of Ant‐DPM and Ant‐7 even though the C(sp 3 )‐C(sp 3 ) σ‐bond length of the σ‐dimers of Ant‐DPM , Ant‐5 , and Ant‐7 (1.567–1.575 Å) are calculated to be close to the normal C(sp 3 )‐C(sp 3 ) σ‐bond length.…”
Section: Resultsmentioning
confidence: 99%
“…[28][29][30][31][32][33] In 2018, Nishiuchi, Kubo,a nd co-workers reported that 10-protected 9-anthryl groups served to furnish an excellently stable radical, 5Mes. [34] Theradical 5H,lacking a10-mesityl group,forms the tail-to-tail s-dimer 6 both in the solid state and in solution with abond dissociation enthalpy of 19.7 kcal mol À1 in toluene,t hus showing the importance of substituents at the 10-position.…”
Section: Triarylmethyl Radicalsmentioning
confidence: 99%
“…Recently, the highly luminescent properties of triarylmethyl radicals were reported as promising materials in organic light‐emitting diodes (OLEDs) . In 2018, Nishiuchi, Kubo, and co‐workers reported that 10‐protected 9‐anthryl groups served to furnish an excellently stable radical, 5Mes . The radical 5H , lacking a 10‐mesityl group, forms the tail‐to‐tail σ‐dimer 6 both in the solid state and in solution with a bond dissociation enthalpy of 19.7 kcal mol −1 in toluene, thus showing the importance of substituents at the 10‐position.…”
Section: Radicals With Bulky Protecting Groupsmentioning
confidence: 99%